The Interplay of Social Media Marketing, Brand Trust, Customer Satisfaction and Loyalty - Walean, Ronny H.; Rantung, Nancy Margaretha; Mandagi, Deske W. (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to understand how social media marketing (SMM) affects customer satisfaction and loyalty in the context of emerging e-commerce markets, with a particular focus on the mediating role of brand tr Purpose: This study aimed to understand how social media marketing (SMM) affects customer satisfaction and loyalty in emerging e-commerce markets, with a particular focus on the mediating role of brand trust. Methodology/approach: This study used a quantitative correlational research design. Data were collected through an online survey of 182 active users of a leading Indonesian e-commerce platform. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software to examine the relationships between SMM, brand trust, customer satisfaction, and loyalty. Results: The study found that SMM had a significant positive impact on brand trust. In turn, brand trust positively influences customer satisfaction and loyalty. Furthermore, brand trust is a critical mediating variable that strengthens the relationship between SMM and customer outcomes. Conclusions: Building brand trust through effective social media engagement is essential for enhancing customer satisfaction and loyalty in e-commerce brands. SMM strategies that foster trust can serve as powerful tools for achieving long-term consumer retention in competitive digital marketplaces. Limitations: This study focused solely on Indonesian users of a single e-commerce platform, which may limit the generalizability of the findings to other markets or platforms. Contribution: This study provides practical insights for marketers, digital strategists, and e-commerce businesses aiming to strengthen consumer relationships. This study contributes to a broader understanding of how social media engagement can be leveraged to build trust and drive loyalty in rapidly growing online markets. ust. Methodology/approach: A quantitative correlational research design was used. Data were collected through an online survey of 182 active users of a leading e-commerce platform in Indonesia. The data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS software to examine the relationships between SMM, brand trust, customer satisfaction, and loyalty. Results/findings: The study found that SMM has a significant positive impact on brand trust. In turn, brand trust positively influences both customer satisfaction and customer loyalty. Furthermore, brand trust acts as a critical mediating variable that strengthens the relationship between SMM and customer outcomes. Conclusions: Building brand trust through effective social media engagement is essential for enhancing customer satisfaction and loyalty in e-commerce. SMM strategies that foster trust can serve as powerful tools for achieving long-term consumer retention in competitive digital markets. Limitations: The study focused solely on Indonesian users of a single e-commerce platform, which may limit the generalizability of the findings to other markets or platforms. Contribution: This study provides practical insights for marketers, digital strategists, and e-commerce businesses aiming to deepen consumer relationships. It contributes to the broader understanding of how social media engagement can be leveraged to build trust and drive loyalty in rapidly growing online markets.